A CAD-Driven and Cloud-Based Autonomous Process Planning Framework for Reconfigurable Bending Press Machines - Eriyeti Murena; Khumbulani Mpofu; Gift Nenzhelele; Wilfred Dube (Proceedings of Engineering and Technology Innovation, 2025)
Sheet metal part manufacturers are increasingly under pressure to meet highly variable consumer demands. As product customization increases, the production process for sheet metal bending parts becomes more complex. This article proposes a fully integrated cloud-based system for sheet metal process planning. The system is developed based on a computer-aided design application and has the capability to rapidly convert a standard for the exchange of product data (STEP) file manufacturing instructions. A new mathematical model for calculating the overall production cycle time is also formulated. Two sheet metal components are used to test the system. The results demonstrate that the proposed cloud-based framework can display the 3D model, its face relationships, and a table containing the manufacturing information.